Enhancing ESG efforts through reporting: how do we minimize greenwashing? (focused on the SGX energy & utilities sector) - Choo, Xuan Zhi (2025)
The integration of Environmental, Social, and Governance (ESG) criteria into corporate strategy has become increasingly crucial as stakeholders demand more sustainable and ethical business practices. However, the concurrent rise of greenwashing—where companies may overstate or inaccurately represent their ESG efforts to appear more environmentally friendly and socially responsible than they actually are—presents a notable challenge. Greenwashing not only undermines stakeholder trust but also jeopardizes the overall credibility of genuine sustainability efforts. This thesis aims to explore how enhanced reporting mechanisms can mitigate the incidence of greenwashing, thereby promoting authentic sustainability practices.